Neo Rauch. - Birnbaum, Daniel; Cooke, Lynne; Szeemann, Harald; van Grevenstein, Alexander; Bonnefantenmuseum, Maastricht (Ostfildern-Ruit : Hatje Cantz Verlag Ostfildern-Ruit, 2002)
Neo Rauch was born in Leipzig in 1960, where he still lives today. He is one of the most original artists of his generation. His paintings appear disturbingly detached and familiar, for their figures, objects and mood seem to come from old advertising posters, dusty book covers or forgotten comics. Rauch's formulistic visual symbols suggest a more profound meaning, yet it is difficult to decipher their message. The tension lurking under the almost frozen surface is fuelled by paradox. As vivid as the structure of the work comes across, the impression is right. As powerful as the broken colours are, they appear faded, of yesterday. In 2002, Neo Rauch will receive The Vincent - The Vincent Van Gogh Award for Contemporary Art - in Maastricht. This publication marks the occasion of this award and forms the first comprehensive presentation of the artist's oeuvre, with 70 works from 1993-2002.
bibliog. p. 140-141
biog., tent. p. 139
Duits
Engels
Neo Rauch, Bonnefantenmuseum, Maastricht, [02.06 - 06.10.2002]
boek
Keywords: Rauch, Neo